Pre-service English Teachers' Expectation and Reality in the Teaching Practicum - Salsabila Pajria Zahra, Salsa (2020)
The purpose of the study is to explore expectation and fulfillment of pre-service teachers in their teaching practicum. Particularly, it explores the pre-service teachers' expectation and the fulfillment of those expectations. It also seeks for the potential causes of unmet expectation and how it affects them. This study employed a case study approach and involved 17 pre-service teachers majoring in English Education and have done the teaching practicum. The instruments used in this study are questionnaire and interview. The findings indicate that there are some expectations of pre-service teachers that were not fulfilled. Also, the data reveal possible factors affecting the pre-service teachers' unmet expectation which are lack of preparation, lack of confidence, inadequate teaching media, learners' low motivation, lack of support, students' behavior, lack of practical knowledge, a sudden and forced switch to online-learning. These unmet expectations have positively and negatively affect them. It is then suggested that there need to be more practical activity during the pre-service teachers' coursework.